Married women in the Irish part-time labour market - Doris, Aedin (Economic & Social Studies, 1998)
This paper uses an econometric analysis of the 1987 Economic and Social Research Institute household survey data to assess the sources of the growth which has occurred in parttime employment in the last decade. The models used allow both for the possibility that the hours of work choice is a discrete one, and for the influence of the demand side of the labour market on a woman's choice between part-time and full-time work. The results confirm the impression gained from descriptive statistics that the growth in part-time employment has been supply-led, but that the growth of the Services sector has facilitated this increase.
Keywords: Married women; Part time employment; Labour market; Ireland; Female employment